Case Study Of Hainan's Tropical Fruits Industry - Wu, Wen Hui (2008)
The aims of this case analysis are to examine the overall condition and performance of Hainan's tropical fruits industry, to investigate the impact of the new trends of world fruit industry on the China's fruit industry especially Hainan's tropical fruits industry.